Dry-state nano electrostatic spinning mask with core-shell structure and spinning process method of dry-state nano electrostatic spinning mask
By adopting a core-shell structure design in the mask, using a water-soluble shell and a water-insoluble core, combined with electrospinning technology, the problems of poor structural stability of the mask, uncontrollable release of effective ingredients and not lasting moisturizing effects are solved, and the multiple functions of the mask and long-term skin care effects are achieved.
Patent Information
- Application Number
- CN202411839448.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The existing electrospinned mask has poor structural stability, uncontrollable release of effective ingredients, and the moisturizing effect is not long-lasting.
A dry nano electrospinning mask designed with a core-shell structure is composed of water-soluble materials, and the inner core is composed of water-soluble materials. It is prepared through electrospinning technology to achieve separation and optimization of structural stability and functional release.
It realizes the structural stability of the mask, the controlled release of active ingredients and the long-term moisturizing effect, significantly improving the efficacy and user experience of the mask.
Smart Images

Figure CN119656067A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a dry nano electrostatic spinning mask, in particular to a dry nano electrostatic spinning mask with a core-shell structure and a spinning process method thereof, wherein the outer shell is a water-soluble material and the inner core is a water-insoluble material, and the mask is suitable for the field of skin care. Background Art
[0002] Facial mask is a product widely used in beauty and skin care. It has many functions such as moisturizing, repairing skin barrier, and anti-oxidation, and is favored by consumers. Traditional facial mask types mainly include non-woven masks, hydrogel masks, and smearable cream masks. Although these masks can provide moisturizing and nutrients to the skin, they still have some limitations. For example, non-woven masks are mostly based on fiber materials. Although they have a simple structure and are easy to produce, they have poor air permeability and fit, making it difficult to achieve deep nutrient delivery to the skin; although hydrogel masks have certain moisturizing and adhesion effects, their mechanical properties are weak, they are easy to slip, and the release rate of active ingredients is uncontrollable.
[0003] In recent years, the development of nanotechnology and polymer materials has provided new ideas for the innovation of facial masks. Nanofibers have become an ideal choice for new facial mask materials due to their high specific surface area, good air permeability and adjustable physical and chemical properties. Electrospinning technology can generate fibers with a diameter of nanometers, which can significantly increase the specific surface area of the mask and improve its contact efficiency with the skin, thereby more effectively delivering effective ingredients. Nanofiber dry masks without preservatives have high safety during use and can effectively reduce potential skin irritation and allergic reactions caused by preservatives. In addition, nano-electrospinning fiber membranes also have good mechanical properties and adjustable structures, and can provide directional release of functional substances under different conditions.
[0004] However, most existing electrospun fiber masks are single-layer structures with a single material, and usually cannot meet the requirements of moisturizing, structural support, and controlled release of functional ingredients at the same time. The water-insoluble fiber membrane lacks an outer layer material that can dissolve in water, making it difficult for functional ingredients to effectively penetrate the skin in a short period of time. As for structural support, traditional instant fiber membranes tend to lose their original shape after dissolution, affecting user experience.
[0005] In response to these problems, the development of a dry nano-electrospinning fiber membrane with a core-shell structure has become a possible solution. The core-shell structure is a composite structure widely used in the fields of materials science and biotechnology. The core part provides mechanical strength or specific functions, and the shell part is used to protect or transfer specific substances. In the present invention, the core-shell structure is applied to the design of the mask. The active ingredients are wrapped in a controllably soluble shell, and the core part is composed of insoluble materials. After the mask meets water, the PVA in the shell can dissolve and release the effective ingredients. At the same time, the gelatin absorbs water and swells, and slowly releases. The rapid release of PVA is combined with the sustained release of gelatin, so that the mask has a sustained release effect. The internal core material uses water-insoluble PVB to maintain the shape and moisturizing properties of the mask. This design not only enables the mask to have better structural support and moisturizing effects, but also enables the rapid release and sustained action of the active ingredients.
[0006] Existing technical solutions focus more on the single function of the material, such as rapid release, structural support or moisturizing. This type of mask has limitations in achieving its functions, and it is difficult to take into account structural stability, sustained release of active ingredients and moisturizing effects. For example, a single-layer fiber membrane may dissolve as a whole or become loose in structure after coming into contact with water, and it is impossible to simultaneously achieve the release of functional ingredients and structural support, and multiple functions cannot be achieved in the same product. Therefore, the development of a dry nanofiber mask that can combine a water-soluble shell layer and a water-insoluble core layer will bring new breakthroughs in the design of mask materials and has important market potential and application prospects.
[0007] Through the present invention, nano-electrospinning technology is cleverly applied to facial mask materials to achieve a combination of moisturizing, functional ingredient release and structural stability. This innovation can significantly improve the efficacy of facial masks, making them better in fit, comfort and long-term moisturizing during use, thereby improving skin absorption and meeting users' demand for efficient skin care products. Summary of the invention
[0008] The purpose of the present invention is to solve the following technical problems in the prior art: 1. The structural stability of the mask is poor: Traditional water-soluble electrospinning mask materials dissolve immediately after absorbing water and cannot maintain the fiber membrane structure, which affects the absorption of effective ingredients and the user's use effect.
[0009] 2. The release of effective ingredients is uncontrollable: The release rate of effective ingredients in existing water-soluble electrospinning masks cannot be accurately controlled. Usually, a large amount of ingredients are released in a short period of time, resulting in waste of ingredients. The skin cannot fully absorb them and cannot achieve sustained efficacy. The effective ingredients of non-water-soluble masks are wrapped by non-water-soluble materials and are difficult to release.
[0010] 3. The moisturizing effect is not long-lasting: Existing electrospinning masks are difficult to effectively lock in moisture. Usually, the moisture in the skin will evaporate quickly within a short period of time after use, making it difficult to provide long-lasting moisturizing, which limits the skin care effect of the mask.
[0011] The present invention aims to solve the above-mentioned technical problems by designing a dry nano electrospinning fiber membrane mask with a core-shell structure, thereby achieving skin care functions of stable structure, controlled release of effective ingredients and long-lasting moisturizing.
[0012] The present invention provides a dry nano electrospun fiber membrane mask with a core-shell structure, which is mainly prepared by electrospinning technology. The outer shell is composed of a water-soluble material, and the inner core is composed of a water-insoluble material, so as to solve the problems of poor structural stability of the mask, uncontrollable release of effective ingredients, and short-lasting moisturizing effect in the prior art.
[0013] The present invention achieves the above objectives through the following technical solutions: The mask adopts a core-shell structure design and consists of two parts: Shell: Made of water-soluble materials, it can dissolve quickly when in contact with water. The shell contains moisturizing ingredients, and by controlling the dissolution rate, the ingredients can be gradually released, avoiding the disadvantage of too fast and unsustainable release of the ingredients.
[0014] Core: Made of non-water-soluble materials, it mainly provides structural support to ensure that the mask can maintain its shape after the outer shell dissolves and continue to provide a physical barrier for the skin. At the same time, the nanofiber structure of the core has a high specific surface area, which helps to absorb and release moisture and functional ingredients, further improving the moisturizing effect.
[0015] The dry nano electrospinning mask with core-shell structure is characterized by: The dry nano electrospinning mask is made by an electrospinning device: The spun yarn constituting the mask has a core-shell structure, including an outer shell and an inner core; the outer shell contains polyvinyl alcohol: gelatin: effective ingredients in a mass ratio of 3-12: 1-10: 0.1-10; the inner core contains polyvinyl butyral: polydimethylsiloxane: glycerol: polyethylene glycol in a mass ratio of 4-10: 2-10: 0.5-5: 2-10.
[0016] Furthermore, the alcoholysis degree of the polyvinyl alcohol is 70-95%; the gel strength of the gelatin is 60-300 Bloomg; wherein the molecular weight of the polyvinyl alcohol is 70,000-250,000Mw; The viscosity of the polydimethylsiloxane at 25° C. is 1 – 500 cSt; The molecular weight of the polyethylene glycol is 120-1000 Mw; The effective ingredients are one or more of sodium hyaluronate, polyglutamic acid, Tremella heteropolysaccharide, glycerin, butylene glycol, ceramide and squalane.
[0017] Furthermore, the solvent of the shell is formic acid, and the solvent of the core is anhydrous ethanol.
[0018] Furthermore, the dry nano electrospinning mask is obtained by coaxial electrospinning technology, and the specific steps are as follows: (1) Injecting the inner core spinning solution and the outer shell spinning solution into different syringes respectively, the inner core spinning solution is injected into the core solution channel of the coaxial electrospinning device (model TL-BM-300 high-voltage electrospinning machine produced by Shenzhen Tongli Micro-Nano Technology Co., Ltd.), and the outer shell spinning solution is injected into the shell solution channel of the coaxial electrospinning device; (2) adding the syringe containing the spinning solution obtained in step (1) into a coaxial double-layer spinneret device; (3) adjusting the flow rate of the inner core and outer shell spinning solutions; (4) The polymer solution solidifies into a fiber membrane on the receiving roller under the action of a high voltage electric field.
[0019] Further, the shell spinning solution is made by the following steps: The polyvinyl alcohol and gelatin are mixed with the formic acid solution and stirred evenly for the first time, and then the functional components are added to the mixed solution and stirred evenly for the second time to obtain a shell spinning solution containing the functional components. After the spinning solution is stirred evenly, it is allowed to stand until bubbles formed by the stirring are discharged to prevent the spinning from being disturbed by the bubbles; The first stirring temperature is 60-90°C, and the stirring time is 2-12 hours; the second stirring temperature is 20-30°C, and the stirring time is 2-12 hours; The core spinning solution is prepared by the following steps: The polyvinyl butyral and anhydrous ethanol solution are mixed and stirred evenly for the first time, and then polydimethylsiloxane, glycerol and polyethylene glycol are added thereto and stirred evenly for the second time to obtain a core spinning solution. After the spinning solution is stirred evenly, it is allowed to stand until bubbles formed by stirring are discharged to prevent the spinning from being disturbed by bubbles; The first stirring temperature is 20-30°C, and the stirring time is 2-12 hours; the second stirring temperature is 20-30°C, and the stirring time is 2-12 hours; Furthermore, the coaxial double-layer spinneret is a coaxial double-layer spinneret composed of two spinnerets of different diameters sleeved together, and the coaxial double-layer spinneret includes an inner core spinneret and an outer shell spinneret, wherein the inner diameter of the inner core spinneret is 0.1-0.7mm; the inner diameter of the outer shell spinneret is 0.2-1mm, and the distance between the outer wall surface of the outer shell spinneret and the inner wall surface of the inner core spinneret is generally 0.05-0.4mm.
[0020] The flow rate of the inner core spinning solution is 0.5 - 2.0 mL / h; the flow rate of the outer shell electrospinning solution is 1.0 -3.0 mL / h; Under the action of the high voltage electric field, the high voltage range is 10 - 30 kV and the receiving distance is 10 - 30 cm; The receiving roller has a rotation speed of 10-200 rpm; The diameter of the receiving roller is 7.5-15 cm; The temperature of the spinning environment is 20-30°C; the humidity is 20-60% RH; Furthermore, during the electrospinning process, the solvents in the shell and the core evaporate, and the fiber membrane finally formed is a dry nanofiber structure; In the above core-shell structure nanofiber mask, the fiber diameter of the nanofiber mask is 300-900nm, the fiber diameter of the core is 100-700nm, the thickness of the mask is 0.2mm-1mm, the porosity is 60-90%, and the porosity (%) = (1-ρmembrane / ρmaterial) × 100, where ρmembrane is the actual density of the fiber membrane, ρmembrane = mmembrane / Vmembrane, where mmembrane is the actual weight of the fiber membrane, Vmembrane is the actual volume of the fiber membrane, and ρmaterial is the theoretical density of the polymer material used in the fiber membrane. Beneficial effects brought by the technical solution of the invention: The present invention adopts a core-shell structure design, which is different from the traditional single-layer structure mask. The outer shell and the inner core have different material properties and functions, which realizes the separation and optimization of structural stability and functional release. In addition, the nanofiber dry mask without adding preservatives has higher safety during use and can effectively reduce potential skin irritation caused by preservatives.
[0021] The water-soluble design of the shell uses a combination of PVA and gelatin to ensure the controlled release of the active ingredients, while the non-water-soluble core material PVB provides continuous structural support and moisturizing functions, which is significantly different from existing mask technology. The water solubility of the shell ensures that when the mask comes into contact with water, PVA can quickly release the encapsulated active ingredients. After this part dissolves, the gelatin that has swelled after absorbing water gradually releases the active ingredients therein, achieving a sustained-release effect and avoiding excessive release at one time, which would cause the skin to not absorb it. The PVB structure of the core can still maintain the mechanical strength of the mask after the shell of the mask dissolves, ensuring that the mask is in close contact with the skin, and its nanofiber structure helps lock in moisture, forming an effective moisturizing barrier, further enhancing the skin care effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The fiber morphology of the fiber membrane of Example 1 of the present invention under a 1500× electron microscope.
[0023] Figure 2 The fiber morphology of the fiber membrane of Example 1 of the present invention under a 100× optical microscope before and after soaking in water.
[0024] Figure 3 The concentration of sodium polyglutamate in the fiber membrane of Example 1 in water changes with the immersion time.
[0025] Figure 4 The concentration of sodium polyglutamate in the fiber membrane of Example 2 in water changes with the immersion time.
[0026] Figure 5 The concentration of sodium polyglutamate in the fiber membrane of Example 3 in water changes with the immersion time.
[0027] Figure 6 The concentration of sodium polyglutamate in water in the fiber membrane of Example 4 changes with the immersion time. Specific implementation plan
[0028] Example 1
[0029] (1) Preparation of shell spinning solution: 7 g of polyvinyl alcohol (PVA) with an alcoholysis degree of 88% and 5 g of gelatin with a gel strength of 180 Bloom g were added to 87.56 g of formic acid, and stirred at 60°C for 4 hours until the mixture was uniformly stirred. Then, 0.3 g of glycerol, 0.07 g of sodium hyaluronate and 0.07 g of sodium polyglutamate were added, and the mixture was stirred at 25°C for 6 hours and allowed to stand until the bubbles were removed.
[0030] (2) Preparation of core spinning solution: 8 g of PVB with a molecular weight of 90,000 - 120,000 Mw was dissolved in 79 g of anhydrous ethanol and stirred at 25°C for 6 hours. After complete dissolution, 6 g of polydimethylsiloxane with a viscosity of 2 cSt, 2 g of glycerol and 5 g of polyethylene glycol with a molecular weight of 400 Mw were added, and stirring was continued for 6 hours. The mixture was allowed to stand until the bubbles were removed.
[0031] (3) Preparation of electrospinning fiber membrane: The fiber membrane was made using a TL-BM-300 high-voltage electrospinning machine produced by Shenzhen Tongli Micro-Nano Technology Co., Ltd. The shell electrospinning solution and the core electrospinning solution obtained in the previous two steps were injected into different 10 ml syringes, and the core spinning solution was injected into the core solution channel of the coaxial electrospinning device. The shell spinning solution was injected into the shell solution channel of the coaxial electrospinning device and added to the coaxial double-layer spinneret device. The core spinneret with an inner diameter of 0.3 mm and the shell spinneret with an inner diameter of 0.7 mm were used. The core flow rate was set to 1.0 mL / h, the shell flow rate was set to 2.0 mL / h, the high-voltage electric field was set to 20 kV, the receiving distance was 20 cm, the receiving drum speed was 60 rpm, and the environmental conditions were a temperature of 25 ° C and a humidity of 35%. The diameter of the collected nanofibers was 300-900nm, the diameter of the core fibers was 100-700nm, the thickness of the fiber membrane was about 0.6mm, and the porosity was 75%. Electron microscopy images of core-shell nanofiber membranes prepared by electrospinning Figure 1 As shown, Figure 2 The fiber morphology of the core-shell nanofiber membrane of this example under an optical fiber microscope in a dry state and after being soaked in water.
[0032] 0.05 g of nanofiber membrane was placed in a sample tube, and then 1 mL of pure water was injected. The immersion time of the nanofiber membrane was controlled. The total test time was 2 hours. Every 20 minutes, the concentration of sodium polyglutamate in the aqueous solution was tested using a high performance liquid chromatograph. The concentration of sodium polyglutamate in water changes with immersion time. Figure 3 shown.
[0033] Example 2
[0034] (1) Preparation of shell spinning solution: 12 g of PVA with an alcoholysis degree of 70% and 6 g of gelatin with a gel strength of 200 Bloom g were added to 81.33 g of formic acid, and stirred at 80°C for 4 hours until the mixture was uniformly stirred. Then, 0.3 g of glycerol, 0.3 g of butylene glycol and 0.08 g of sodium polyglutamate were added, and the mixture was stirred at 25°C for 6 hours and allowed to stand until the bubbles were removed.
[0035] (2) Preparation of core spinning solution: Dissolve 10g of PVB with a molecular weight of 70,000 - 100,000 Mw in 77g of anhydrous ethanol and stir at 25°C for 6 hours. After complete dissolution, add 4g of polydimethylsiloxane with a viscosity of 300cSt, 5g of glycerol and 4g of polyethylene glycol with a molecular weight of 700Mw, continue stirring for 6 hours, and let it stand until the bubbles are removed.
[0036] (3) Preparation of electrospinning fiber membrane: The fiber membrane was made using a TL-BM-300 high-voltage electrospinning machine produced by Shenzhen Tongli Micro-Nano Technology Co., Ltd. The shell electrospinning solution and the core electrospinning solution obtained in the previous two steps were injected into different 10 ml syringes, and the core spinning solution was injected into the core solution channel of the coaxial electrospinning device. The shell spinning solution was injected into the shell solution channel of the coaxial electrospinning device and added to the coaxial double-layer spinneret device. The core spinneret with an inner diameter of 0.4 mm and the shell spinneret with an inner diameter of 0.8 mm were used. The core flow rate was set to 1.2 mL / h, the shell flow rate was set to 2.0 mL / h, the high-voltage electric field was set to 22 kV, the receiving distance was 20 cm, the receiving drum speed was 70 rpm, and the environmental conditions were a temperature of 27 ° C and a humidity of 40%. The diameter of the collected nanofibers was 400-900 nm, the diameter of the core fiber was 150-350 nm, the thickness of the fiber membrane was about 0.6 mm, and the porosity was 75%.
[0037] 0.05 g of nanofiber membrane was placed in a sample tube, and then 1 mL of pure water was injected. The immersion time of the nanofiber membrane was controlled. The total test time was 2 hours. Every 20 minutes, the concentration of sodium polyglutamate in the aqueous solution was tested using a high performance liquid chromatograph. The concentration of sodium polyglutamate in water changes with immersion time. Figure 4 shown.
[0038] Example 3
[0039] (1) Preparation of shell spinning solution: 3 g of PVA with an alcoholysis degree of 95% and 7 g of gelatin with a gel strength of 60 Bloom g were added to 88.63 g of formic acid and stirred at 70°C for 6 hours until the mixture was uniformly stirred. Then, 0.3 g of glycerol, 1 g of ceramide and 0.08 g of sodium polyglutamate were added and stirred at 25°C for 6 hours and allowed to stand until the bubbles were removed.
[0040] (2) Preparation of core spinning solution: Dissolve 4g of PVB with a molecular weight of 170,000 - 250,000 Mw in 72g of anhydrous ethanol and stir at 25°C for 6 hours. After complete dissolution, add 10g of polydimethylsiloxane with a viscosity of 1cSt, 4g of glycerol and 10g of polyethylene glycol with a molecular weight of 120Mw. Continue stirring for 6 hours and let it stand until the bubbles are removed.
[0041] (3) Preparation of electrospinning fiber membrane: The fiber membrane was prepared using a TL-BM-300 high-voltage electrospinning machine produced by Shenzhen Tongli Micro-Nano Technology Co., Ltd. The shell electrospinning solution and the core electrospinning solution obtained in the previous two steps were injected into different 10 ml syringes, and the core spinning solution was injected into the core solution channel of the coaxial electrospinning device. The shell spinning solution was injected into the shell solution channel of the coaxial electrospinning device and added to the coaxial double-layer spinneret device. The core spinneret with an inner diameter of 0.5 mm and the shell spinneret with an inner diameter of 0.9 mm were used. The core flow rate was set to 1.0 mL / h, the shell flow rate was set to 2.5 mL / h, the high-voltage electric field was set to 25 kV, the receiving distance was 25 cm, the receiving drum speed was 100 rpm, and the environmental conditions were a temperature of 30 ° C and a humidity of 40%. The diameter of the collected nanofibers was -500 - 900nm, the diameter of the core fiber was 200 -400nm, the thickness of the fiber membrane was about 0.7 mm, and the porosity was 70%.
[0042] 0.05 g of nanofiber membrane was placed in a sample tube, and then 1 mL of pure water was injected. The immersion time of the nanofiber membrane was controlled. The total test time was 2 hours. Every 20 minutes, the concentration of sodium polyglutamate in the aqueous solution was tested using a high performance liquid chromatograph. The concentration of sodium polyglutamate in water changes with immersion time. Figure 5 shown.
[0043] Example 4
[0044] (1) Preparation of shell spinning solution: 10 g of PVA with an alcoholysis degree of 88% and 1 g of gelatin with a gel strength of 300 Bloom g were added to 86.63 g of formic acid, and stirred at 75°C for 4 hours until the mixture was uniformly stirred. Then, 0.3 g of glycerol, 2 g of squalane and 0.05 g of sodium polyglutamate were added, and the mixture was stirred at 25°C for 6 hours and allowed to stand until the bubbles were removed.
[0045] (2) Preparation of core spinning solution: 7 g of PVB with a molecular weight of 120,000-150,000 Mw was dissolved in 88.5 g of anhydrous ethanol and stirred at 25°C for 6 hours. After complete dissolution, 2 g of polydimethylsiloxane with a viscosity of 500 cSt, 0.5 g of glycerol and 2 g of polyethylene glycol with a molecular weight of 1000 Mw were added, and stirring was continued for 6 hours. The mixture was allowed to stand until the bubbles were removed.
[0046] (3) Preparation of electrospinning fiber membrane: The fiber membrane was made using a TL-BM-300 high-voltage electrospinning machine produced by Shenzhen Tongli Micro-Nano Technology Co., Ltd. The shell electrospinning solution and the core electrospinning solution obtained in the previous two steps were injected into different 10 ml syringes, and the core spinning solution was injected into the core solution channel of the coaxial electrospinning device. The shell spinning solution was injected into the shell solution channel of the coaxial electrospinning device and added to the coaxial double-layer spinneret device. The core layer spinneret with an inner diameter of 0.4 mm and the shell layer spinneret with an inner diameter of 0.8 mm were used. The flow rate of the core layer was set to 1.5 mL / h, the flow rate of the shell layer was set to 2.5 mL / h, the high-voltage electric field was set to 20 kV, the receiving distance was 20 cm, the receiving drum speed was 60 rpm, and the environmental conditions were a temperature of 20 ° C and a humidity of 35%. The diameter of the collected nanofibers was -400 - 800nm, the diameter of the core fiber was 150 - 350nm, the thickness of the fiber membrane was about 0.5 mm, and the porosity was 75%.
[0047] 0.05 g of nanofiber membrane was placed in a sample tube, and then 1 mL of pure water was injected. The immersion time of the nanofiber membrane was controlled. The total test time was 2 hours. Every 20 minutes, the concentration of sodium polyglutamate in the aqueous solution was tested using a high performance liquid chromatograph. The concentration of sodium polyglutamate in water changes with immersion time. Figure 6 shown.
[0048] Comparative Example 1
[0049] (1) Preparation of spinning solution: 8 g of PVA with an alcoholysis degree of 88% and 2 g of gelatin with a gel strength of 180 Bloom g were added to 89.56 g of formic acid, and stirred at 85°C for 4 hours until the mixture was uniformly stirred. Then, 0.3 g of glycerol, 0.07 g of sodium hyaluronate and 0.07 g of sodium polyglutamate were added, and the mixture was stirred at 25°C for 6 hours and allowed to stand until the bubbles were removed.
[0050] (2) Preparation of electrospinning fiber membrane: The fiber membrane was prepared using a TL-BM-300 high-voltage electrospinning machine produced by Shenzhen Tongli Micro-Nano Technology Co., Ltd. The electrospinning solution obtained in the previous step was injected into a 10 ml syringe, and a spinneret with an inner diameter of 0.34 mm was used. The spinning solution flow rate was set to 1.0 mL / h, the high-voltage electric field was set to 20 kV, the receiving distance was 20 cm, the receiving drum speed was 90 rpm, and the environmental conditions were a temperature of 25 ° C and a humidity of 35%. The diameter of the collected nanofibers was 300-600 nm, the thickness of the fiber membrane was about 0.6 mm, and the porosity was 70%, and an instant nanofiber membrane was prepared for comparison.
[0051] Comparative Example 2
[0052] (1) Preparation of spinning solution: The fiber membrane was prepared using a TL-BM-300 high-voltage electrospinning machine produced by Shenzhen Tongli Micro-Nano Technology Co., Ltd. 8 g of PVB with a molecular weight of 90,000-120,000 Mw was dissolved in 80 g of anhydrous ethanol and stirred at 25°C for 6 hours. After complete dissolution, 7 g of polydimethylsiloxane with a viscosity of 2 cSt, 1 g of glycerol and 4 g of polyethylene glycol with a molecular weight of 400 Mw were added, and stirring was continued for 2 hours. The mixture was allowed to stand until the bubbles were removed.
[0053] (2) Preparation of electrospinning fiber membrane: The electrospinning solution obtained in the previous step was injected into a 10 ml syringe, and a spinneret with an inner diameter of 0.34 mm was used. The spinning solution flow rate was set to 1.0 mL / h, the high voltage electric field was set to 8 kV, the receiving distance was 15 cm, the receiving drum speed was 90 rpm, and the environmental conditions were a temperature of 25 ° C and a humidity of 35%. The diameter of the collected nanofibers was 500-800 nm, the thickness of the fiber membrane was about 0.6 mm, and the porosity was 75%, and a non-water-soluble nanofiber membrane was prepared for comparison.
[0054] The fiber membrane of Comparative Example 1 is a water-soluble fiber membrane, which will dissolve and release immediately after contacting water and lose its fiber structure; the solvent of the fiber membrane of Comparative Example 2 is ethanol, and sodium polyglutamate is insoluble in ethanol, so Comparative Examples 1 and 2 were not subjected to sustained-release experiments.
[0055] Figure 3 – Figure 6 Corresponding to the trend of the concentration of sodium polyglutamate in the solution changing with the immersion time in the fiber membranes of Examples 1 to 4, the sodium polyglutamate in the mask is slowly released in the first 15 minutes and is basically completely released after 20 minutes, while the general usage time of the mask is 15 to 20 minutes. The results show that the nanofiber dry mask of the present invention has a sustained release effect during use.
[0056] Hydration and moisturizing effect test: The fiber membranes of the above six embodiments and two comparative examples were respectively applied to the faces of volunteers with dry skin. First, the face was cleaned and dried, and distilled water was sprayed on the face using a spray bottle with a water volume of about 0.5 ml. The fiber membrane of the present invention was cut into 5×5 cm in size and applied to the wet face, and then 1 ml of distilled water was sprayed until the fiber membrane completely fit the face. Three groups of experiments were performed on each fiber membrane. After applying for 20 minutes, it was peeled off and Real The Bubee skin moisture tester measures the moisture content of the facial skin stratum corneum before spraying water, and the moisture mass content of the skin stratum corneum 0h, 2h, and 4h after peeling off. The results are shown in Table 1. The results show that compared with the water-soluble fiber membrane of Comparative Example 1, the core-shell fiber membrane of the present invention will not lose its durability due to too rapid dissolution when replenishing water; although the instant membrane has a rapid hydrating effect, it loses water faster; and the sustained-release design of the core-shell membrane of the present invention provides the skin with a more balanced and lasting hydration effect; compared with the non-water-soluble fiber membrane of Example 2, the core material in the core-shell fiber membrane is not easy to dissolve completely, and can form a breathable moisturizing film on the skin surface, which helps to lock in moisture. Compared with the insoluble fiber membrane, this design reduces the problem of excessive moisture barrier, while providing an appropriate water vapor permeability to maintain normal breathing of the skin.
[0057] Table 1 shows the moisture content of skin keratin
Claims
1. A dry nano electrospinning mask with a core-shell structure, characterized in that: The dry nano electrospinning mask is made by an electrospinning device: The spun yarn constituting the mask has a core-shell structure, including an outer shell and an inner core; the outer shell contains polyvinyl alcohol: gelatin: effective ingredients in a mass ratio of 3-12: 1-10: 0.1-10; the inner core contains polyvinyl butyral: polydimethylsiloxane: glycerol: polyethylene glycol in a mass ratio of 4-10: 2-10: 0.5-5: 2-10.
2. The dry nano electrospinning facial mask with a core-shell structure according to claim 1, characterized in that: The alcoholysis degree of the polyvinyl alcohol is 70-95%; the gel strength of the gelatin is 60-300 Bloomg; wherein the molecular weight of the polyvinyl alcohol is 70,000-250,000Mw; The viscosity of the polydimethylsiloxane at 25° C. is 1 – 500 cSt; The molecular weight of the polyethylene glycol is 120-1000 Mw; The effective ingredients are one or more of sodium hyaluronate, polyglutamic acid, Tremella heteropolysaccharide, glycerin, butylene glycol, ceramide and squalane.
3. The dry nano electrospinning facial mask with a core-shell structure according to claim 1, characterized in that: The solvent of the shell is formic acid, and the solvent of the core is anhydrous ethanol.
4. A spinning process for the dry nano electrospinning mask with a core-shell structure according to claim 1, The dry nano electrospinning mask is obtained by coaxial electrospinning technology, and the specific steps are as follows: (1) Injecting the inner core spinning solution and the outer shell spinning solution into different syringes respectively, the inner core spinning solution is injected into the core solution channel of the coaxial electrospinning device, and the outer shell spinning solution is injected into the shell solution channel of the coaxial electrospinning device; (2) adding the syringe containing the spinning solution obtained in step (1) into a coaxial double-layer spinneret device; (3) adjusting the flow rate of the inner core and outer shell spinning solutions; (4) The polymer solution solidifies into a fiber membrane on the receiving roller under the action of a high voltage electric field.
5. The spinning process of the dry nano electrospinning mask with a core-shell structure according to claim 4, characterized in that: The shell spinning solution is made by the following steps: The polyvinyl alcohol and gelatin are mixed with the formic acid solution and stirred evenly for the first time, and then the functional components are added to the mixed solution and stirred evenly for the second time to obtain a shell spinning solution containing the functional components. After the spinning solution is stirred evenly, it is allowed to stand until bubbles formed by the stirring are discharged to prevent the spinning from being disturbed by the bubbles; The first stirring temperature is 60-90°C, and the stirring time is 2-12 hours; the second stirring temperature is 20-30°C, and the stirring time is 2-12 hours; The core spinning solution is prepared by the following steps: The polyvinyl butyral and anhydrous ethanol solution are mixed and stirred evenly for the first time, and then polydimethylsiloxane, glycerol and polyethylene glycol are added thereto and stirred evenly for the second time to obtain a core spinning solution. After the spinning solution is stirred evenly, it is allowed to stand until bubbles formed by stirring are discharged to prevent the spinning from being disturbed by bubbles; The first stirring temperature is 20-30°C, and the stirring time is 2-12 hours; the second stirring temperature is 20-30°C, and the stirring time is 2-12 hours.
6. The spinning process of the dry nano electrospinning facial mask with a core-shell structure according to claim 5, characterized in that: The coaxial double-layer spinneret is a coaxial double-layer spinneret composed of two spinnerets of different diameters, and the coaxial double-layer spinneret comprises an inner core spinneret and an outer shell spinneret, wherein the inner diameter of the inner core spinneret is 0.1-0.7 mm; the inner diameter of the outer shell spinneret is 0.2-1 mm, and the distance between the outer wall surface of the outer shell spinneret and the inner wall surface of the inner core spinneret is generally 0.05-0.4 mm; The flow rate of the inner core spinning solution is 0.5 - 2.0 mL / h; the flow rate of the outer shell electrospinning solution is 1.0 - 3.0 mL / h; Under the action of the high voltage electric field, the high voltage range is 10 - 30 kV and the receiving distance is 10 - 30 cm; The receiving roller has a rotation speed of 10-200 rpm; The receiving roller has a diameter of 7.5 – 15 cm; The temperature of the spinning environment is 20-30°C; the humidity is 20-60%RH.
7. The spinning process of the dry nano electrospinning facial mask with a core-shell structure according to claim 5 or 6, characterized in that: During the electrospinning process, the solvents in the shell and the core evaporate, and the fiber membrane finally formed is a dry nanofiber structure; In the above-mentioned core-shell structure nanofiber mask, the fiber diameter of the nanofiber mask is 300-900nm, the fiber diameter of the inner core is 100-700nm, the thickness of the mask is 0.2mm-1mm, the porosity is 60-90%, and the porosity (%) = (1-ρmembrane / ρmaterial) × 100, where ρmembrane is the actual density of the fiber membrane, ρmembrane = mmembrane / Vmembrane, where mmembrane is the actual weight of the fiber membrane, Vmembrane is the actual volume of the fiber membrane, and ρmaterial is the theoretical density of the polymer material used in the fiber membrane.